Analysis and modification of natural red spinel by ion beam techniques for jewelry applications - D. Bootkul (2018)
© 2016 Elsevier B.V. Natural spinel (MgAl2O4) can be found in several colors resembling corundum, i.e. rubies and sapphires. In particular, spinels with saturated red appearance, called spinel-rubies or balas rubies, are the most appreciated. However, the beautiful rich red spinels are very rare, they can be found in a range of pastel shades blended with either brown, orange or purple. Therefore, the objectives of the present studies are to investigate the origins of the color blending and to improve the optical property of this gemstone by ion beam techniques. Two non-destructive ion beam analysis techniques, i.e., particle induced X-ray emission (PIXE) and iono-luminescence (IL), have been employed for geochemical analysis of the gems. As an alternative method, ion beam treatment using N2-ion was applied for improving optical appearance and color enhancement of the red Burmese (Myanmar) spinel. For each run, samples were implanted at ion energy of 70 keV to a fluence of ~ 1 × 1017 ions/cm2and subsequently surface cleaning. UV-Vis spectroscopy, Raman spectroscopy and photoluminescence spectroscopy were selected for sample characterization. As for comparison, the spinel samples from the same origin were heated in air and undergone the same measurement. We have found that the color appearance of spinel can be engineered by both techniques. However, the heating has transformed the normal or the ordered spinel to the inverse or the disordered one, and thus disorder might be used as criteria to determine if the stone has been heated. On the other hand, the crystalline structure of the spinel remains almost the same or slightly disordered after ion implantation. This finding leads to future applications for jewelry.